COMPUTATION OF THE AVERAGE MASS THERMAL CONDUCTIVITY OF OAK FURNITURE ELEMENTS SUBJECTED TO CONVECTIVE HEATING BEFORE LACQUERING (Innovation in Woodworking Industry and Engineering design, 2026)
A methodology for the computation and research of the following two mutually connected problems has been suggested: 1D non-stationary temperature distribution in subjected to unilateral convective heating process of flat wooden furniture elements before lacquering and change in their average mass thermal conductivity. For the realization of the methodology, created earlier by the authors 1-dimensional nonlinear mathematical model has been solved for the transient heat conduction in the furniture elements during their unilateral convective heating. The model contains a mathematical description of the average mass thermal conductivity of the elements and their surface layer, which is intended for lacquering. For the numerical solution of the model with the aim of applying the methodology a software program has been prepared and input in the calculation environment of Visual FORTRAN Professional. Using the program, computations have been carried out for determination of the 1-dimensional non-stationary temperature distribution along the elements’ thickness and of the average mass thermal conductivity for flat oak furniture elements with an initial temperature of 20 oC, moisture content of 8 %, thickness of 16 mm, width of 0.6 m, and length of 1.2 m during their 10 min unilateral convective heating at temperature of the processing air medium of 100 oC, which circulates above the elements with a velocity of 2 m·s-1, 5 m·s-1, and 8 m·s-1 aimed at improvement of the conditions for the subsequent lacquering. During the computations a temperature of 20 oC for the surrounding air near the non-heated surface of the carrying rubber band has been used. The change in the average mass thermal conductivity of the studied furniture oak elements and also of their heated surface layers during the heating is graphically presented and analyzed.Because of the wide range of applications, the need for paulownia is constantly increasing.